Preparation and preliminary application of fluorescent microsphere test strips for feline parvovirus antibodies - Jinyuan Shang; Manping Yan; Xiaohao Zhang; Wei Liu; Shun Wu; Zhenjun Wang; Li Yi; Chunxia Wang; Erkai Feng; Yuening Cheng; Guoliang Luo (BMC Biotechnology, 2024)
Abstract This study introduces a novel diagnostic modality for the detection of feline panleukopenia virus (FPV) antibodies in feline serum by using fluorescent microsphere immunochromatographic test strips (FM-ICTS). Leveraging the inherent specificity of antigen-antibody interactions, the FM-ICTS approach demonstrates considerable potential for efficient and accurate FPV antibody detection within a short timeframe. The FM-ICTS method demonstrates strong diagnostic performance, with consistent accuracy and stability over time. PBS buffer dilution enables detection across the range of FPV antibody haemagglutination inhibition (HI) titres in both healthy and immunized or infected cats. A high correlation (R² = 0.9733) between the T/C ratio and FPV antibody titres confirms the method’s effectiveness in quantifying these titres. Clinical validation with 84 samples supports its reliability by matching results with HI assays. Additionally, stability tests show that the test strips maintain performance during storage, with a coefficient of variation (CV) below 12% over three months at 25℃. This innovative FM-ICTS framework emerges as a promising avenue for expedient and dependable disease diagnosis within the realm of veterinary science, offering implications for timely disease management and surveillance.